Revealing the Structural Basis of Promiscuous Amine Transaminase Activity. Issue 1 (8th November 2012) - Steffen‐Munsberg, Fabian; Vickers, Clare; Thontowi, Ahmad; Schätzle, Sebastian; Meinhardt, Tina; Svedendahl Humble, Maria; Land, Henrik; Berglund, Per; Bornscheuer, Uwe T.; Höhne, Matthias
<x xml:space="preserve">Abstract</x> One lock for different keys: A flexible arginine in the active site allows γ‐aminobutyrate:pyruvate transaminases to bind the chemically different substrates L‐alanine and γ‐aminobutyric acid. Moreover, a flexible arginine residue facilitates the promiscuous conversion of (S)‐amines and ketones. The degree of promiscuity can be related to distinct key amino acids lying at the surface of the active site.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>